A new method for field dynamic balancing of rigid motorized spindles based on real-time position data of CNC machine tools - Zhang, Longfei; Zha, Jun; Zou, Chao; Chen, Xiaoyan; Chen, Yaolong (International journal of advanced manufacturing technology, 2019)
In high-speed precision machining, the spindle balance state may be altered by re-clamping of the workpiece or tool changes, as well as a number of other reasons. Therefore, repeating the dynamic balancing process on-site after any changes have been made to the spindle system is of utmost importance. This paper proposes a new method for balancing rigid motorized spindles based on the real-time position data of CNC machine tools with the aim of reducing the costs associated with external balancing instruments and improving the efficiency of the dynamic balancing process. Moreover, the proposed technique can be integrated into CNC controllers and data such as the amplitude and phase angle of spindle can be extracted based on the real-time position of linear axis with the feed direction perpendicular to the spindle axis. The speed of the spindle and the reference position of the correction masses can then be calculated using the index pulse of the spindle measurement system and unbalanced spindle data. The dynamic balancing system was shown to accurately identify sensitive processing speeds of motorized spindles, which is crucial to high-speed high-precision machining. Finally, the feasibility and the stability of the spindle dynamic balancing system were experimentally validated using an LDT500 ultra-precision diamond turning. The roughness of the machined surface was shown to decrease from 25.2 to 5.9 nm and thus, verifies the feasibility of applying spindle dynamic balancing system in practical engineering.